Regulation and organizational forms of internal audit of health care facilities - I.V. (Економіка, управління та адміністрування)
Internal audit is the main form of control, which is a functionally independent assessment of the activities of health care institutions in order to provide recommendations and advice aimed at improving the activities, and the management of economic processes of the institution. The introduction of internal audit for health care institutions of Ukraine will help to use more efficiently not only budget funds, but also improve the health care system as a whole, thus bringing the medical sector in the country to a new level, namely equating to international and European standards.